2021
DOI: 10.1038/s41598-021-85260-z
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the interactions and dynamics of a DES formed by phenyl propionic acid and choline chloride

Abstract: Deep eutectic solvents (DESs) have received much attention in modern green chemistry as inexpensive and easy to handle analogous ionic liquids. This work employed molecular dynamics techniques to investigate the structure and dynamics of a DES system composed of choline chloride and phenyl propionic acid as a hydrogen bond donor and acceptor, respectively. Dynamical parameters such as mean square displacement, liquid phase self-diffusion coefficient and viscosity are calculated at the pressure of 0.1 MPa and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(9 citation statements)
references
References 65 publications
0
9
0
Order By: Relevance
“…Role of HBD can be played by acids, which can endow a DES with unique properties [ 68 , 220 , 221 , 222 , 223 , 224 ]. Fu et al [ 220 ] developed a DES based on acrylic acid and estimated the stability of the ChCl-acrylic acid complexes by QM calculations.…”
Section: Main Directions Of Investigationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Role of HBD can be played by acids, which can endow a DES with unique properties [ 68 , 220 , 221 , 222 , 223 , 224 ]. Fu et al [ 220 ] developed a DES based on acrylic acid and estimated the stability of the ChCl-acrylic acid complexes by QM calculations.…”
Section: Main Directions Of Investigationsmentioning
confidence: 99%
“…These DESs can be used to enhance the solubility of active ingredients, membrane transport, drug delivery, and bioavailability [ 225 , 226 ]. Saha et al [ 222 ] used combined DFT/MD simulations to study the possibility of developing DESs based on acetylsalicylic acid (aspirin), and Bonab et al [ 223 , 224 ] simulated DESs based on ChCl and phenyl propionic acid, which have a wide variety of uses including cosmetics, food additives, and pharmaceuticals [ 227 ]. The authors aimed to understand the physical mechanisms occurring at the eutectic composition point.…”
Section: Main Directions Of Investigationsmentioning
confidence: 99%
See 1 more Smart Citation
“…This includes properties such as density, viscosity, and diffusion coefficients . More complex evaluations of liquid structure and dynamic behavior of common DESs have been performed with traditional nonpolarizable force fields, such as the OPLS, CHARMM/CGenFF, ,, and AMBER/GAFF ,, families. Of these force fields, only OPLS has been specifically tuned for DESs .…”
Section: Introductionmentioning
confidence: 99%
“…Abranches et al reported that the CT behavior of the chloride anion is responsible for the formation and properties of these mixtures . Similarly, to optimize the design of type I DESs for a particular chemical process, further information about their structural, physicochemical, and transport properties, as well as their relationship to temperature, is required, allowing for the accurate design of a task-specific solvent for a variety of applications . The knowledge related to the interactions between choline chloride and metal halide salts is limited.…”
Section: Introductionmentioning
confidence: 99%